Pendidikan Keperawatan Dan Interprofessional Education Dalam Meningkatkan Kompetensi Kolaboratif Tenaga Kesehatan: Literatur Review - Siti Zahara Nasution; Oasenea Melliany; Evi Karota Bukit; Rika Endah Nurhidayah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Modern nursing education requires not only clinical competence but also interprofessional collaborative skills. A lack of collaboration among healthcare professionals can reduce the quality of healthcare services and compromise patient safety. Interprofessional Education (IPE) is implemented to develop teamwork skills and enhance understanding of professional roles during the educational process. Objective: This study aimed to analyze the effectiveness of Interprofessional Education (IPE)-based nursing education in improving the collaborative competencies of healthcare professionals. Methods: This study employed a systematic literature review using the PRISMA approach. Literature was obtained from Google Scholar, PubMed, and ScienceDirect databases published between 2020 and 2024 and selected based on relevance and quality criteria. Of the 50 identified articles, 10 articles were included and analyzed descriptively to assess the effectiveness of IPE in improving the collaborative competencies of healthcare professionals. Results: The findings showed that IPE effectively improves communication, teamwork, understanding of professional roles, and patient safety. Learning methods such as clinical simulation, blended learning, and interprofessional discussions support the development of collaborative competencies. However, its implementation is still challenged by curriculum limitations, institutional readiness, and the need for educator training. Conclusion: Interprofessional Education (IPE) is an effective and relevant strategy in nursing education for enhancing collaborative competencies and improving the quality of holistic healthcare services.